Spinal Health during Unloading and Reloading Associated with Spaceflight - Green, David A.; Scott, Jonathan P. R. (Frontiers in Physiology, 2018)
Spinal elongation and back pain are recognised effects of exposure to microgravity, however, spinal health has received relatively little attention. This changed with the report of an increased risk of post-flight intervertebral disc (IVD) herniation and subsequent identification of spinal pathophysiology in some astronauts post-flight. Ground-based analogues, particularly bed rest, suggest that a loss of spinal curvature and IVD swelling may be factors contributing to unloading-induced spinal elongation. In flight, trunk muscle atrophy, in particular multifidus, may precipitate lumbar curvature loss and reduced spinal stability, but in-flight (ultrasound) and pre- and post-flight (MRI) imaging have yet to detect significant IVD changes. Current International Space Station missions involve short periods of moderate-to-high spinal (axial) loading during running and resistance exercise, superimposed upon a background of prolonged unloading (microgravity). Axial loading acting on a dysfunctional spine, weakened by anatomical changes and local muscle atrophy, might increase the risk of damage/injury. Alternatively, regular loading may be beneficial. Spinal pathology has been identified in-flight, but there are few contemporary reports of in-flight back injury and no recent studies of post-flight back injury incidence. Accurate routine in-flight stature measurements, in- and post-flight imaging, and tracking of pain and injury (herniation) for at least two years post-flight. These should be complemented by ground-based studies, in particular hyper buoyancy floatation (HBF) a novel analogue of spinal unloading, in order to elucidate the mechanisms and risk of spinal injury, and to evaluate countermeasures for exploration where injury could be mission critical.